Leading Women in Spanish Cinema and Television in the Long 1970s - Faulkner, Sally; Triana-Toribio, Núria (Bloomsbury Publishing (US), 2026)
This open access book offers a feminist cultural history of Spain of the 1970s, exploring the work of women in the audio-visual industries who joined the workforce in significant numbers over this decade of Transition from the Franco dictatorship, to a democracy that enshrined gender equality in its constitution of 1978. Leading Women in Spanish Cinema and Television in the Long 1970s seeks the work of women in new places and analyses it in new ways. Rejecting the director- auteur approach, which has endured for over seventy-five years in both Film and Television Studies - despite the fact that it tends to occlude the work of women - the authors look instead at below-the-line roles in cinema, and at television. In particular, they investigate editing, forgotten or overlooked areas of television broadcasting, such as children’s programming, and film activism in the period, such as in the co-operative Drac Màgic: in these places the work of women can be found. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The Arts and Humanities Research Council.